6th International Week of Science, Technology and Innovation. (July 2020) - Rojas-Suárez, J P; Velásquez-Pérez, T; Sandoval-Amador, A; Dueñas Ramírez, L M; V-Niño, E D
Abstract : The 6th International Week of Science, Technology and Innovation (6th IWSTI), which took place from 19 to 22 November 2019, in the city of San José de Cúcuta, Colombia, and was organized by the "Universidad Francisco de Paula Santander", San José de Cúcuta" and "Seccional Ocaña". This event was aimed at the academic and scientific community and the productive sectors of the region. The objective of the 6 edition of the International Week of Science, Technology, and Innovation was to disseminate the advances in research and extension of national and international institutions, through seedbeds and research groups, promoting the participation of the productive sectors in research, extension, and technological development and innovation activities, which contribute to the strengthening of the University-Business-Government relationship. List of Organizing Committee, International Scientific Committee, National Scientific Committee, Logistics Committee and Sponsors are available in this pdf.